The impact of COVID-19 on the IT sector: Was the adjustment as easy as it seemed? The case of Croatia - Julia Perić; Ružica Stanić (Economic Review: Journal of Economics and Business, 2022)
The crisis caused by the Covid-19 pandemic affected almost all organizations, regardless of the industry in which they operate. The new working conditions created to protect the health of all employees required a new mindset and a 'switch' to more digitalized operations. Many organizations had to adapt or even completely change their business model in order to survive and save jobs. Since digitalized operations were already in place in the IT industry, it seemed that organizations within it had an easier adjustment process to the new pandemic conditions. But have IT companies survived the pandemic as unscathed as it seemed? The purpose of this paper is to examine how Croatian IT companies mitigated the effects of Covid-19 and how they managed their employees during this crisis. This paper examines the impact of the pandemic on employees in the IT sector and analyzes how leaders managed to ensure the psychological safety of their employees under these uncertain conditions. In addition, this paper answers whether and to what extent IT companies had to adapt their business models and what other challenges (cybersecurity, new platforms, etc.) they had to respond to. Using questionnaires and semi-structured interviews, managers and employees of ten IT companies operating in Croatia were surveyed. It was found that most IT companies experienced a short-term decline in revenue during the pandemic. The results of the research showed that companies in the IT sector also organized remote work, but unlike other sectors, employees in the IT sector were more likely to permanently switch to remote work, as they were more satisfied, motivated and productive when working remotely. Moreover, adapting to the new working conditions led IT companies to accelerate digitalization and reduce operating costs without reducing the quality of services. This research can serve as an example of good practice for all organizations looking to digitalize their business and respond to potential new, unexpected crises.
Keywords: D80; 330; Covid-19; IT sector; remote work; managing employees; digitalization